Orexin dual receptor antagonists, zolpidem, zopiclone, eszopiclone, and cognitive research: A comprehensive dose-response meta-analysis - Zhou, Mengzhen; Tang, Jiyou; Li, Shasha; Li, Yaran; Zhao, Mengke (Frontiers in Human Neuroscience, 2023)
ABSTRACT Background About 1/3 of adults report mild to severe difficulties in falling asleep or maintaining sleep. A large number of studies have shown that long-term use of hypnotics can cause brain dysfunction and damage cognition. Objective To evaluate whether low, medium and high doses of Orexin dual receptor antagonists (DORA), Zopiclone (zop), Eszopiclone (esz) and Zolpidem (zst) can impair cognition. Methods PubMed, Embase, Scopus, Cochrane Library, Google Scholars were searched from inception to 20 September 2022. Randomized controlled trials (RCTs) assessing therapeutic effects of DORA,Eszopiclone,Zopiclone and Zolpidem for sleep and cognitive function were included. The primary outcomes were indices related to Cognitive profile, including memory, alertness, execution and control function, and attention and orientation, etc.The secondary outcomes were indices related to sleep and adverse events. Standard Mean difference (SMD) was generated for continuous variables. Certain data were captured from figures by GetData 2.26 and analyzed by RStudio 4.2. Results Finally, a total of 8702 subjects were included in 29 studies. Compared with placebo, the DSST (Digit Symbol Substitution Test) score of low/medium dose/high-dose DORA was respectively (SMD=0.77, 95% CI: 0.33 to 1.20; SMD=1.58, 95% CI: 1.11 to 2.05; SMD=0.85, 95% CI: 0.33 to 1.36). The DSST scale score of Zolpidem at low/medium/high dose was respectively (SMD=- 0.39, 95% CI: - 0.85 to 0.07; SMD=- 0.88, 95% CI: - 2.34 to 0.58; SMD=- 0.12, 95% CI: - 0.85 to 0.60). Zopiclone's DSST scale score (SMD=-0.18, 95% CI: -0.54 to 0.18). In addition, the total sleep time (TST) of low/medium/high dose DORA was respectively (SMD=0.28, 95% CI: - 0.15 to 0.70; SMD=1.36, 95% CI: 0.87 to 1.86; SMD=2.59, 95% CI: 1.89 to 3.30). Conclusion We recommend Dora as the best intervention for insomnia, which is highly effective in inducing and maintaining sleep without impairing cognition. Although Zolpidem has a more pronounced effect on maintaining sleep, it is best to reduce its use because of its side effects. Eszopiclone, Zopiclone improved sleep performance, but its safety in terms of cognition remains to be verified.